Genetic structure and diversity of the giant frog (Limnonectes blythii) in northern Thailand - Suwannapoom C. (2014)
The aim of this study is to analyse genetic diversity, structure and differentiation of the giant frogs (Limnonectes blythii). One hundred and sixty four individuals from 4 populations in Mae Hong Son Province, Thailand were used for the analysis of genetic polymorphism at 7 microsatellite loci. The collection showed considerable polymorphism with observed number of alleles per locus ranging for seven different loci, with an average of 3.4 alleles per locus. Mean genetic diversity of the four populations with moderate level, but in populations with lower genetic diversity. Furthermore, the NJ tree approach clustering conWrmed the results of PAM is more differentiated than the others. The signiWcant levels of genetic structure among the sites were found in which could be resulting from isolation by distance rather than a position relative to habitat. The results of this study indicate that genetic structure could be useful for evaluation of neutral genetic variation particularly as the basis for inferring population and species capacity for species conservation and management decisions. © Maxwell Scientific Organization, 2012.